The impact of COVID-19 on chronic pain - Lavin, Abraham; LeBlanc, Félix; El Helou, Antonios (Frontiers in Pain Research, 2023)
A reduced quality of life is often a hefty burden that those with chronic pain are left to bear. During the global pandemic caused by COVID-19, a complex relationship to study was that of the impact of COVID-19 on chronic pain, which is the interest of this review of literature from PubMed and Google Scholar and other selected articles according to relevance. We will briefly describe the epidemiologic facts and risk factors, followed by the proposed pathophysiologic mechanisms. We will then cover therapeutic avenues regarding various molecules and their possible interaction, the most promising being those whose mechanism of action can be directly tied to the pathophysiologic aspects of the condition. Finally, we will describe the approach to a chronic pain patient who consults during the pandemic.